Involuntary facial expression processing: extracting information from two simultaneously presented faces. - Samantha Baggott (Public Library of Science (PLoS), 2011)
Facial expressions play an important role in successful social interactions, with previous research suggesting that facial expressions may be processed involuntarily. In the current study, we investigate whether involuntary processing of facial expressions would also occur when facial expression distractors are simultaneously presented in the same spatial location as facial expression targets. Targets and distractors from another stimulus class (lions) were also used. Results indicated that angry facial expression distractors interfered more than neutral face distractors with the ability to respond to both face and lion targets. These findings suggest that information from angry facial expressions can be extracted rapidly from a very brief presentation (50 ms), providing compelling evidence that angry facial expressions are processed involuntarily.